113 Cost-Utility of Revisions for Cervical Deformity Correction Warrants Minimization of Reoperations. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Horn, Samantha R; Passias, Peter G; Lafage, Renaud; Lafage, Virginie; Smith, Justin S; Line, Breton G; Mundis, Gregory M; Kelly, Michael P; Protopsaltis, Themistocles; Kim, Han Jo; Bortz, Cole; Segreto, Frank; et al.
Abstract: INTRODUCTION: Cervical deformity (CD) surgery has become increasingly more common and complex, which has also led to reoperations for complications such as distal junctional kyphosis (DJK). Cost-utility analysis has yet to be used to analyze CD revision surgery in relation to the cost-utility of primary CD surgeries. METHODS: Retrospective review. CD defined as at least 1 of the following: C2 to C7 Cobb > 10°, CL > 10°, cSVA > 4 cm, CBVA > 25°. Quality-adjusted life years (QALY) were calculated by EQ5D and utilized a 3% discount rate to account for residual decline of life expectancy (men: 76.9 yr, women: 81.6 yr). Medicare reimbursement at 30 d assigned costs for index procedures (9+ level posterior fusion, 4-8 level posterior fusion with anterior fusion, 2-3 level posterior fusion with anterior fusion, 4-8 level anterior fusion) and revision fusions (2-3, 4-8, or 9+ level posterior refusion). Main outcome was cost per QALY. RESULTS: Eighty-nine CD patients included (62 yr, 65% F). CD correction involved 7.7 ± 3.7 levels fused, with 34% combined approach, 49% posterior-only, 17% anterior-only, 20.2% 3-column osteotomy. Costs for index surgeries ranged from $20 001 to $55 205, with the average cost of $44 318 and cost per QALY of $27 267. Eleven revision surgeries (10.3 levels fused) occurred up to 1 yr, with an average cost of $41 510. Indications for revisions were DJK (5/11), neurological impairment (4), infection (1), prominent/painful instrumentation (1). Average QALYs gained were 1.62 per revision patient. Cost was $28 138 per QALY for reoperations. CONCLUSION: CD revisions had a cost of $28 138 per QALY, in addition to $27 267 per QALY for primary CD surgeries. For primary CD patients, CD surgery has the potential to be cost effective, with the caveats of the durability of the surgery and that a patient livelihood extends long enough to have the benefits. Efforts in research and surgical technique development should emphasize minimization of reoperation causes such as DJK that significantly affect cost-utility of these surgeries to bring cost-utility to an acceptable range.